A STUDY OF ENTREPRENEURIAL MARKETING OF SMALL AND MEDIUM ENTERPRISE (SMES) IN â€œKIOS ANYAMAN BAMBU LENGKOANâ€ DESA KINILOW-TOMOHON - Runtulalo, Fransisca Nikita (Sam Ratulangi University, 2015)
ABSTRACT Small and Medium Enterprise (SMEs) play an important role to development of national economy. The study aims to identif the entrepreneurial marketing problems faced and formulating the success factors by this SMEs. This research is conducted in â€œKios Anyaman Bambu Lengkoanâ€ Desa Kinilow-Tomohon. Qualitative methodology by in-depth interview, and Descriptive-Exploratory study are used to conducted this research. â€œSocial situationâ€ as the population. The business owner is a informant for this research. The results is â€œKios Anyaman Bambu Lengkoanâ€ still faces regarding on Attention from Government, Capital access and Paying of wages, and Less of promotion. Than, SMEs success factors which come from Government support, Capital access, Appropriates marketing strategies, Innovative productivity, Businessâ€™ vision and mission, Entrepreneurâ€™s future plans, and Customer satisfaction. To deals those SMEs problems faces is only comes as a result of initiatives by the business owner itself and Government. Keywords: SMEs-handicraft-entrepreneurial marketing-success factors